Ler e jogar ou jogar e ler? : estratégias de leitura empregadas por estudantes do 5º ano do ensino fundamental ao jogar no click jogos - Boeira, Adriana Ferreira (My University, 2016)
The purpose of this investigation is to explore the reading profile of fifth-year children in a private elementary school in the city of Vacaria, checking the reading strategies used by them while playing on the website Click Jogos. This investigation is supported by Larrosa’s reflexions (2002, 2003, 2011), Freire’s (1987, 2003) and Soares’ (2002, 2005) regarding the reading; Chantier’s (1998, 2002a, 2002b), Lévy’s (1996, 2001) and Bakhtin’s (2003, 2004) regarding the supports and reading enunciations; Santaella’s (2004, 2014a, 2014b, 2014c), Solé’s (1998), Kato’s (1999) and Kleiman’s (2008) regarding the different reader styles and reading strategies and Huizinga’s (2000), Caillois’ (1990) Mattar’s (2010) and Primos’ (2003a, 2003b) regarding the game itself. The methodological approach used is empirical, of qualitative character, from content analysis (BARDIN, 2004), showing the organizing, coding and categorizing process of the corpus, composed by enunciations produced in two moments in the computer laboratory in school X, thus registered: a) in the online survey, twenty participants in the same date and time, this sought to identify the preferred websites and select the one that would be used in the next step of the research; b) the audio and video verbal protocols (ERICSSON; SIMON, 1993) selected, when four of the participants, male and female, with distinct ages, individually in different time and dates, clearly related the actions and the procedures they executed, while reading and interacting with games of their interests in Click Jogos. After transcribing the selected verbal protocols, were identified and named four categories, gathering and analyzing the enunciations of the subjects that: a) show the path travel up to Click Jogos; b) evince how they choose the games; c) show the responsive position (BAKHTIN, 2003, 2004) and the reading strategies and browsing through hypertexts, scanning if the experience is revealed (LARROSA, 2002, 2003, 2011); d) show how they leave Click Jogos. The fifth-year students of elementary school uncover before, or simultaneously the printed enunciations, the enunciations that belong to their readout of the world (FREIRE, 1987, 2003) and precedes the word reading, showed in different types of screens (desktop, notebook, tablet and smartphone). These readers, when reading in different screens, elect as reading material the digital games, composed by hypertexts, verbal enunciations, visual (static or moving) sonorous and hybrid. The reading through the digital game represents a challenge to the reader; so, when playing, he might assume responsive position, taking responsibility, placing himself, acting and using different reading and browsing strategies: scanning the screen, browse, look for the target, holding himself at the reading enunciations; also, selects, anticipates, infers and control everything that is read. Yet, this reading might enable appropriation, invention, production of meanings and directions to the hypertext by the reader.
O objetivo desta pesquisa é investigar o perfil de leitura dos estudantes do 5º ano do Ensino Fundamental de uma escola particular do município de Vacaria-RS, analisando as estratégias de leitura empregadas por eles ao jogar no site Click Jogos. A investigação apoia-se nas reflexões de Larrosa (2002, 2003, 2011), Freire (1987, 2003) e Soares (2002, 2005) sobre a leitura; de Chartier (1998, 2002a, 2002b), Lévy (1996, 2001) e Bakhtin (2003, 2004) a respeito dos suportes e enunciados de leitura; de Santaella (2004, 2014a, 2014b, 2014c), Solé (1998), Kato (1999) e Kleiman (2008) acerca dos diferentes tipos de leitores e das estratégias de leitura e de Huizinga (2000), Caillois (1990), Mattar (2010) e Primo (2003a, 2003b) sobre o jogo. A abordagem metodológica empregada é empírica, de caráter qualitativo, a partir da análise de conteúdo (BARDIN, 2004), mostrando o processo de organização, codificação e categorização do corpus, composto pelos enunciados produzidos em dois momentos, no laboratório de informática do Colégio X, assim registrados: a) no questionário online, por vinte participantes, no mesmo dia e horário, que buscava identificar os sites preferidos deles e selecionar aquele que seria utilizado na próxima etapa da pesquisa; b) nos protocolos verbais (ERICSSON; SIMON, 1993) de áudio e vídeo selecionados, quando quatro participantes, do gênero masculino e feminino, com idades distintas, individualmente, em datas e horários diferentes, relataram com clareza as ações, os procedimentos que executaram, enquanto liam e interagiam com jogos do seu interesse no Click Jogos. A partir da transcrição dos protocolos verbais selecionados, foram identificadas e nomeadas quatro categorias, reunindo e analisando os enunciados dos sujeitos que: a) demonstram o caminho percorrido até o Click Jogos; b) evidenciam como escolhem os jogos; c) mostram a posição responsiva (BAKHTIN, 2003, 2004) e as estratégias de leitura e navegação diante dos hipertextos, examinando se revelam a experiência (LARROSA, 2002, 2003, 2011); d) demonstram como saem do Click Jogos. Os estudantes do 5º ano do Ensino Fundamental desvendam antes, ou simultaneamente aos enunciados impressos, os enunciados que fazem parte da sua leitura do mundo (FREIRE, 1987, 2003) e que antecede a leitura das palavras, exibidos em diferentes tipos de telas (desktop, notebook, tablet e smartphone). Esses leitores, ao ler em telas, elegem como material de leitura os jogos digitais, compostos de hipertextos, enunciados verbais, visuais (estáticos ou em movimento), sonoros e híbridos. A leitura por meio do jogo digital representa um desafio ao leitor; assim, ao jogar, ele pode assumir posição responsiva, responsabilizando-se, pondo-se, agindo e empregando diferentes estratégias de leitura e navegação: escaneia a tela, navega, busca o seu alvo e detém-se nos enunciados de leitura; também seleciona, antecipa, infere e controla o que lê. Ainda, essa leitura pode possibilitar apropriação, invenção, produção de significados e sentidos ao hipertexto pelo leitor.
Keywords: Leitura; Leitura - Desenvolvimento; Jogos eletrônicos; Reading; Development reading; Electronic games